STRUKTUR JARINGAN INTERKONEKSI, TAHAPAN PEMBANGUNAN E-GOVT DAN FAKTOR YANG MEMPENGARUHI PENERAPAN STRUKTUR JARINGAN INTERKONEKSI (Survai Tentang Interkoneksi di kalangan Aparatur Instansi pelayanan publik bidang informasi dan dokumentasi) - Ari Cahyo Nugroho (BPSDMP Kominfo Jakarta, 2016)
This study first asks questions about the implementation of the interconnection network structure in the public service agencies in the field of information and documentation. Both questioned the influence of the quality of the development stages of e-govt on the quality of the implementation of the interconnection network structure and the third about the other factors that affect the implementation of the interconnection network structure among public service agencies. The findings showed problems related to the first and based on respondents' awareness of Interconnection Network structure adopted in the institution where they work, their agencies were divided into three categories Interconnection Network Structure, LAN; MAN; and WAN. However Interconnection Network Structure category more dominant LAN adopted in Bengkulu and Jambi. In the province of Bangka Belitung dominant Interconnection Network Structure category MAN. While the agency adopters of internet network structure and network without wires is not found none. Related to the second problem, the agency they were divided into four categories, namely: Preparation; Maturation; Consolidation and Utilization. Stages of E-government level appears most prominent Preparations have been done in three research sites. While the agency has reached the stage of utilization, not many. The number of establishments that have reached the stage of utilization exist in Bengkulu and the province of Bangka Belitung. Statistical test results one tail bivariate with SPSS 17.0 by size Pearson association, shows that the relationship among variables